GERMINATION POTENTIAL AND SEEDLING PERFORMANCE OF YELLOW MUSTARD IN ARSENIC CONTAMINATED HYDROPONIC CULTURE - LAKSHMIKANTI BHOI; DULLAV BHOSAGAR; P. C. MISHRA (The Bioscan, 2012)
In the present study, short term hydroponic culture experiments using cotton soaked with sodium arsenite and arsenic contaminated poultry dung suspension have been conducted on yellow mustard. In poultry dung average pH, conductivity, organic matter, nitrate, phosphate and arsenic content were found as 7.25± 0.59, 1.25± 0.08mS, 218.4± 32.7mg/g, 2.57± 0.17mg/g, 21.44 ±4.47mg/g, and 0.038±32.7mg/g respectively. In sodium arsenite contaminated culture with arsenic concentration ranging from 0.5 to 10ppm, maximum seed germination was found in 0.5ppm As (83.33%) and minimum in 10ppm (10 %). Germination Index (GI), Relative Growth Index (RGI) and Quality Index (QI) also showed a maximum of 62%, 77.77% and 0.0108% respectively at 0.05ppm As in arsenic contaminated culture. Poultry dung suspension (PDS) culture showed 100% seed germination in 1% and 5% poultry dung suspension (PDS) and in 10%, 25% and 50% the germination was found as 93.33%, 93.33% and 86.66% respectively with a maximum of 111.95% GI, 114.28% RGI and 0.366% QI at 1%, 5% and 10% PDS respectively. Thus PDS culture was favourable for germination and seedling potential of mustard.